ANALYSIS FACTORS THAT FORM CUSTOMER LOYALTY AT RETAIL STORES IN KUTOARJO - Ivan Setiawan; Eric Harianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Kutoarjo Store. The variables assumed to form consumer loyalty are price, product, service, place, promotion, and presentation. The researcher uses quantitative descriptive research. The population in this study are consumers who shop at least three times at RIA Stores. The sample in this study were consumers who were included in the criteria set by the researchers with a total of 107 people. The analytical method used in this study is explanatory factor analysis (EFA) with the help of the SPSS application. The results of this study indicate that 6 factors are formed, namely Product Arrangement Factors in Stores (1), Product Availability Factors (2), Store Location Factors (3), Store Service Factors (4), Product Pricing Factors (5), Store Promotion Factors (6). The Product Arrangement Factor in the Store has the highest variance value, which is 32.872%. Steps that RIA stores can take are making a list of products and designing product arrangements according to type, adding product variants, creating parking lines, conducting regular employee training, surveying competitors' prices, and starting online promotions. Keywords: Consumer loyalty, Price, Product, Service, Place, Promotion and Presentation